From Generation to Generation: The Role of Grandparents in the Intergenerational Transmission of (Non-)Voting - Elisabeth Gidengil; Hannu Lahtinen; Hanna Wass; Jani Erola (SAGE Publications Inc., 2022)
The literature on the reproduction of political participation across generations has focused almost exclusively on parental effects. Yet, other family members may plausibly play an important role as well. This study explores the role of grandparents in the intergenerational transmission of the propensity to vote. Grandparental effects are theorized in terms of both social learning and status transmission. The analysis takes advantage of a unique dataset that links official turnout data for grandparents, parents, and adult grandchildren with demographic and socioeconomic information from administrative sources. Even controlling for a variety of status-related characteristics, grandchildren are significantly less likely to vote when their grandparents are non-voters. The association between grandparental turnout and the turnout of their adult grandchildren is only partly explained by the mediating effect of parental turnout. Having non-voting grandparents appears to reinforce the effect of having parents who do not vote and may even offset the effects of having parents who are both voters. These results suggest that it is time to take the role of grandparents seriously if we want to understand how political disadvantage is transmitted across generations.